PENGARUH STRESS PADA MOTIVASI PEGAWAI DI CINTA BUDAYA MEDAN - KUANDI; NICHOLAS . (LP2MTBM MAKARIOZ, 2020)
Citra Budaya Medan is one of the institutions under the auspices of the education and culture department of the North Sumatra Province, where this institution has a duty and responsibility in introducing the culture and tourism that da in the North Sumatra Province in general and in particular the culture of the City of Medan. In carrying out his duties, in the Citra Budaya Medan made a high procedure and workload on each of its officers in order to attract tourists to visit Medan City as well as to the North Sumatra Province. In addition, there is a very heavy task for the officers in the Field Cultural Citra in introducing the culture that exists in the North Sumatra province to other country, where the burden of this task is not easy, thus increasing the stress of the officers about the target of the work to be realized. This situation greatly influenced the motivation of the officers in achieving the target of work to be completed, which is for the number of tourists to increase and the culture that exists in the North Sumatra Province is not only known throughout Indonesia, but also in other country, where in reality there is no arts and culture of the North Sumatra Province known to the People of other country. The data analysis on this study used validity and reliability tests, simple linear regression analysis and hypothetical tests, such as determination coefficients and t-tests, where the population in this study was a consumer of 41 Cinta Budaya's employees, whereas the method of sample withdrawal on this study used a census method whose sample numbered 41 people. The results of this study state that the work stress variable has an insignificant effect on the motivation decisions of officers in performing their duties in the Citra Budaay Medan.